Soil Test Based Fertilizer Recommendation for Targeted Yield of French Bean (Phaseolus vulgaris) under Rice-French Bean Cropping System - Pogula, Sowmya; Truptimayee,; Mishra, Antaryami; Saren, Subhashis; Dey, P. (International Journal of Bio-resource and Stress Management, 2016)
A field experiment was conducted during 2014–2015 to study the response of French bean (Phaseolus vulgaris) to graded doses of fertilizer and to formulate soil test based fertilizer recommendation for targeted yield of french bean under rice-french bean cropping system in a lateritic soils of Odisha. Detailed morphological and physico-chemical properties of a typifying pedon of the experimental site was conducted. In kharif season, three fertility gradient strips were created (B-I, B-II & B-III) by application of no fertilizer, recommended dose of fertilizer and twice of the recommended dose in rice. Each of these fertility gradient strips were divided into 24 sub-plots where 21 plots were treated with different treatment combinations of N, P and K, two plots received 2.5 and 5.0 t ha-1 and one plot was kept as absolute control. French bean (cv. Anupam) was grown in these sub-plotsfor investigation during rabi. Highest pod yield, uptake of N, P and K of french bean was achieved in B-III block. Mean pod yield varies from 57.6 to 75.0 q ha-1 whereas, uptake of N, P and K vary from 67.9 to 75.0, 49.0 to 56.6 and 69.9 to 84.9 kg ha-1 respectively. Targeted yield equations for french bean were developed using the Ramamoorthy’s targeted yield approach for site specific integrated nutrient management.